Rising utilization of inpatient pediatric asthma pathways. (1st February 2018) - Kaiser, Sunitha V.; Rodean, Jonathan; Bekmezian, Arpi; Hall, Matt; Shah, Samir S.; Mahant, Sanjay; Parikh, Kavita; Morse, Rustin; Puls, Henry; Cabana, Michael D.; ,
ABSTRACT: Introduction : Clinical pathways are detailed care plans that operationalize evidence-based guidelines into an accessible format for health providers. Their goal is to link evidence to practice to optimize patient outcomes and delivery efficiency. It is unknown to what extent inpatient pediatric asthma pathways are being utilized nationally. Objectives : (1) Describe inpatient pediatric asthma pathway design and implementation across a large hospital network. (2) Compare characteristics of hospitals with and without pathways. Methods : We conducted a descriptive, cross-sectional, survey study of hospitals in the Pediatric Research in Inpatient Settings Network (75% children's hospitals, 25% community hospitals). Our survey determined if each hospital used a pathway and pathway characteristics (e.g. pathway elements, implementation methods). Hospitals with and without pathways were compared using Chi-square tests (categorical variables) and Student's t-tests (continuous variables). Results : Surveys were distributed to 3–5 potential participants from each hospital and 302 (74%) participants responded, representing 86% (106/123) of surveyed hospitals. From 2005–2015, the proportion of hospitals utilizing inpatient asthma pathways increased from 27% to 86%. We found variation in pathway elements, implementation strategies, electronic medical record integration, and compliance monitoring across hospitals. Hospitals with pathways had larger inpatient pediatric programs [mean 12.1 versus 6.1 full-time equivalents, p = 0.04] and were more commonly free-standing children's hospitals (52% versus 23%, p = 0.05). Conclusions : From 2005–2015, there was a dramatic rise in implementation of inpatient pediatric asthma pathways. We found variation in many aspects of pathway design and implementation. Future studies should determine optimal implementation strategies to better support hospital-level efforts in improving pediatric asthma care and outcomes.